Elimination or resurgence: modelling lymphatic filariasis after reaching the 1% microfilaremia prevalence threshold - Prada, JM; Davis, EL; Touloupou, P; Stolk, WA; Kontoroupis, P; Smith, ME; Sharma, S; Michael, E; de Vlas, SJ; Hollingsworth, TD (Oxford University Press, 2019)
The low prevalence levels associated with lymphatic filariasis elimination pose a challenge for effective disease surveillance. As more countries achieve the World Health Organization criteria for halting mass treatment and move on to surveillance, there is increasing reliance on the utility of transmission assessment surveys (TAS) to measure success. However, the long-term disease outcomes after passing TAS are largely untested. Using 3 well-established mathematical models, we show that low-level prevalence can be maintained for a long period after halting mass treatment and that true elimination (0% prevalence) is usually slow to achieve. The risk of resurgence after achieving current targets is low and is hard to predict using just current prevalence. Although resurgence is often quick (<5 years), it can still occur outside of the currently recommended postintervention surveillance period of 4-6 years. Our results highlight the need for ongoing and enhanced postintervention monitoring, beyond the scope of TAS, to ensure sustained success.